2010
DOI: 10.1111/j.1469-8749.2010.03612.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cerebral palsy in very preterm infants: the EPIPAGE prospective population‐based cohort study

Abstract: IPHIntraparenchymal haemorrhage IVH Intraventricular haemorrhage PPROM Preterm premature rupture of membranes PTL Preterm labour PVL Periventricular leucomalacia AIM The aim of this study was to assess the independent role of cerebral lesions on ultrasound scan, and several other neonatal and obstetric factors, as potential predictors of cerebral palsy (CP) in a large population-based cohort of very preterm infants.METHOD As part of EPIPAGE, a population-based prospective cohort study, perinatal data and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(119 citation statements)
references
References 26 publications
4
108
1
6
Order By: Relevance
“…Limited data suggest quantifiable sex differences in CC development at near-term age (4,34). Male gender is associated with increased risk of adverse outcomes, including CP, following preterm birth (35), although males and females did not differ in neurodevelopmental outcome in this study. Associations between CC microstructure, sex, and neurodevelopment warrant further investigation in larger populations to explain risk factors that may increase morbidity among VLBW males.…”
Section: Corpus Callosumcontrasting
confidence: 61%
“…Limited data suggest quantifiable sex differences in CC development at near-term age (4,34). Male gender is associated with increased risk of adverse outcomes, including CP, following preterm birth (35), although males and females did not differ in neurodevelopmental outcome in this study. Associations between CC microstructure, sex, and neurodevelopment warrant further investigation in larger populations to explain risk factors that may increase morbidity among VLBW males.…”
Section: Corpus Callosumcontrasting
confidence: 61%
“…Although major advances in the care of premature infants have resulted in striking improvements in the survival of very low birth weight infants (<1.5 kg), improved survival has been accompanied by a significant increase in the number of pre-term survivors with long-term neurological deficits [7]. The major consequences of this injury are permanent motor impairment (i.e., cerebral palsy [CP]) ranging from mild to profound spastic motor deficits [8][9][10][11][12][13], as well as a broad spectrum of cognitive, social behavioral, attentional, visual, and learning disabilities that manifest by school age in 25 to 50% of children [14][15][16][17][18]. In preterm survivors, magnetic resonance image (MRI)-defined WMI, but not gray matter injury manifests in the first months of life as abnormal movements that are predictive of CP [19][20][21].…”
mentioning
confidence: 99%
“…Recently, infant male sex was considered a risk factor for HIE (Wu et al, 2010) and was associated with an increased development of cerebral palsy in very preterm infants (Beaino et al, 2010). Although the biological basis of this increased risk of brain injury in male babies is not completely understood, several preclinical studies have demonstrated sex-dependent differences in the mechanisms of cell death after HIE.…”
Section: Neuroprotective Strategies For Hiementioning
confidence: 99%